Exploring the spatial variation of food poverty in Ecuador - Farrow, Andrew; Larrea, C; Hyman, Glenn G.; Lema, G (2005)
We examine the geographic dimensions of food consumption in Ecuador, which has one of the highest rates of chronic infant undernutrition in Latin America. We use statistical and spatial analyses to examine the distribution of food consumption and food poverty and to test and generate hypotheses of food poverty estimates at the district level. Results show that the food poor are concentrated in certain locations with a significant cluster identified in the central Andean region. Geographically weighted regression shows that the processes underlying food poverty in Ecuador are also spatially variable. While our results lend support for nationwide land tenure reforms, in the central Andes these must take into account productivity constraints and communal ownership. Improvements in transport infrastructure will likely decrease levels of food poverty country-wide but could be most beneficial in the extreme south and in the province of Esmeraldas. Investment in rural enterprise development should be encouraged in all regions.